Kibble–Zurek Scaling during Defect Formation in a Nematic Liquid Crystal. Issue 7 (13th February 2017) - Fowler, Nicholas; Dierking, Dr Ingo
Abstract: Symmetry‐breaking phase transitions are often accompanied by the formation of topological defects, as in cosmological theories of the early universe, superfluids, liquid crystals or solid‐state systems. This scenario is described by the Kibble–Zurek mechanism, which predicts corresponding scaling laws for the defect density ρ . One such scaling law suggests a relation ρ ≈ τ Q −1/2 with τ Q the change of rate of a control parameter. In contrast to the scaling of the defect density during annihilation with ρ ≈ t −1, which is governed by the attraction of defects of the same strength but opposite sign, the defect formation process, which depends on the rate of change of a physical quantity initiating the transition, has only rarely been investigated. Herein, we use nematic liquid crystals as a different system to demonstrate the validity of the predicted scaling relation for defect formation. It is found that the scaling exponent is independent of temperature and material employed, thus universal, as predicted. Abstract : Finding fault : The Kibble–Zurek scaling for defect formation is confirmed for a nematic liquid crystal system, where the transition from a uniform state to a defect state was achieved by electric field application. A scaling exponent of α =1/2 was obtained for different materials and independent of temperature.